Do preterm infants always have flattened heads?. Issue 5 (May 1993) - Rutter, N; Hinchliffe, W; Cartlidge, P H
Abstract : It has previously been shown that a soft mattress lessens the degree of head flattening that occurs in preterm infants in the early weeks of life. A follow up study of 31 infants of < 32 weeks' gestation found head flattening had resolved by 3-4 years of age, regardless of the type of mattress used in the neonatal period, and the children had heads similar in shape to full term controls.